2011
DOI: 10.5012/bkcs.2011.32.5.1613
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Co(II), Ni(II) and Cu(II) Complexes from Schiff base Ligand and Reactivity Studies with Thermosetting Epoxy Resin

Abstract: A hybrid thermosetting maleimido epoxy compound 4-(N-maleimidophenyl) glycidylether (N-MPGE) containing Co(II), Ni(II) and Cu(II) ions was prepared by curing N-MPGE and tetradentate Schiff base Co(II), Ni(II) and Cu(II) complexes. The curing polymerization reaction of N-MPGE with metal complexes as curing agents was studied. The cured samples were studied for thermal stability, chemical (acid/alkali/solvent) and water absorption resistance and homogeneity of the cured systems. The tetradentate Schiff base, 3-[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Isatin is an endogenous indole whose derivatives are widely used as reagent and chelating agent towards metal ions [21][22][23]. The use of isatin having diketo functionality can provide better binding with metal ions by electrostatic attraction in its nanoaggregate form.…”
Section: Introductionmentioning
confidence: 99%
“…Isatin is an endogenous indole whose derivatives are widely used as reagent and chelating agent towards metal ions [21][22][23]. The use of isatin having diketo functionality can provide better binding with metal ions by electrostatic attraction in its nanoaggregate form.…”
Section: Introductionmentioning
confidence: 99%
“…This study indicates that the metal ion intake decreased [26] (Table.4 ).This order can be explained by Pearson's proposal, hard acid preferred to combine with hard base and soft acid prefered to combine with soft base [27] . It was found that the interaction of Ni(II) is normally more intense than other divalent metal ion with Schiff base ligand [28] .…”
Section: Metal Ion Intakementioning
confidence: 95%
“…Pour the reaction product in ice,(1+2) Schiff base ligand was obtained [10] . The precipated yellow compound was filtered washed with water and dried over unhydrous calcium chloride.…”
Section: Synthesis Of Schiff Base Ligand With Dfmpm and L-glutaminementioning
confidence: 99%
“…The versatility and flexibility of Schiff base compounds having, acyl, aryl and heteroaryl Schiff bases have additional donor sites >C=O, >C=N-, and so on. It has made the Schiff base to function as excellent complexing agents that form multifarious complexes with several transition and inner transition metals and has strengthened the attention of many researchers [1]. Schiff-bases may function as mono-, di-, tri-, or tetradentate ligands depending on the number of coordinating atoms present in the molecule and can construct usually five or six membered chelate rings upon reaction with a metal ion [2].…”
Section: Introductionmentioning
confidence: 99%